Hospital hygiene in Mongolia and the MeshHp project - Popp, Walter (International Journal of Infection Control, 2013)
Mongolia is a vast country between Russia and China with a small population of about 2.7 million people. Hospital hygiene is on a rather low level at the moment. Main problems are infectious diseases and above all a high rate of hepatitis carriers in the general population as well as hospital staff. As part of a German-Mongolian cooperation of both Ministries of Health a project was initiated in 2010 to improve hospital hygiene in some pilot hospitals in Ulaanbaatar, Mongolia. Some success has been achieved after two years, like vaccination of hospital staff against hepatitis B, using alcoholic hand rub on wards and training of staff.